Pengolahan Kripik Bayam Untuk Mewujudkan Agro Industry di Desa Kota Bahagia Kecamatan Kuala Batee Kabupaten Aceh Barat Daya - Dewi Fithria ,Rahmi Fida Sari,Adja Muhammad Daud, Husni Lubis, Riyat, Mauliddin Fajri, Hasnati Murit (Jurnal Pengabdian Agro and Marine Industry, 2025)
The 23rd Regular KKN activity of Teuku Umar University was carried out in Kota Bahagia Village, Kuala Batee District, Southwest Aceh Regency, with a focus on optimizing village resources in order to realize sustainable economic and social resilience.The method used is a participatory approach through observation, interviews, and implementation of work programs. The main programs implemented include making trash cans from used paint buckets, producing organic fertilizer from dry leaves, and innovating agricultural processing in the form of spinach chips. The results of the study showed that the KKN program had a positive impact on the community, especially in increasing awareness of waste management and environmental cleanliness. In addition, product innovation based on village potential opens up new business opportunities that contribute to improving the community's economy. With this program, it is hoped that the community can continue to develop local potential independently and sustainably.Keywords : Real WorkLecture(;)Community Empowerment (;)EnvironmentalManagement(;)Creative Economy(;)Sustainable Agriculture.